Improved fault location on distribution network based on multiple measurements of voltage sags pattern - Awalin, L.J.; Mokhlis, Hazlie; Halim, A.H.A. (2012)
An improvement of fault location algorithm to locate a faulted section for Three Phase to Ground Fault based on multiple measurements is presented in this paper. A new ranking approach is proposed to overcome multiple faulted section candidates. A large scale 11 kV network which comprises of 43 nodes and 5 branches are used to evaluate the proposed algorithm. The result shows that there is improvement in terms of faulted section detection in the first attempt for each additional measurement. An accurate fault distance is also achieved through averaging the fault distance from each measurement.